Ten years of housing estate rehabilitation in Budapest - Szabó, Balázs (Hungarian Geographical Bulletin, 2013)
At the turn of the millennium about one third of the inhabitants of Budapest lived at housing estates. Since then this rate has slightly declined because of new constructions. Demographic trends have also contributed to the decrease of the share of population living on housing estates. The rate of ageing is especially high in case of the older housing estates, nevertheless, the share of the families with children has still remained above average. The rehabilitation of large housing estates seems to be the best way to avoid their demographic erosion and social decline. This paper explores the rehabilitation initiatives carried out in Budapest in the last decade, with special attention to their outcomes, and their effects. We also examine whether renovations resulted in some new socio-spatial differentiations at large housing estates.